Salicylic acid restricts mercury translocation by activating strong antioxidant defense mechanisms in sweet pepper (Capsicum annum L.) - Muhammad Fasih Khalid (10652246) (2023)
Mercury (Hg) availability in soil and its absorption in plants is seriously concerned for plant production and human health. Salicylic acid (SA) is one of the major plant hormones involved in plant growth and development under biotic and abiotic stress conditions. So, the experiment was designed to assess the effect of SA on sweet pepper (Capsicum annum L.) seedlings grown under different Hg toxicity concentrations. Spraying of 100 μ M SA at three different Hg levels, i.e., 0 μ M, 50 μ M, 100 μ M, and 150 μ M. The maximum decrease in photosynthetic machinery, plant growth attributes (shoot length, root length, no. of leaves, fresh and dry biomass (shoot and root)), and more accumulation of Hg in leaves, roots, and fruits of sweet pepper. Additionally, SA significantly reduced the reduction in photosynthetic attributes and plant growth, and increased antioxidant enzymes (SOD, POD, and CAT) under Hg toxicity. H2O2 was found to be lower in plants treated with SA under Hg toxicity than in non-treated plants. The SA application also restricts the accumulation of Hg in sweet pepper roots, leaves, and fruits. Hg translocation in leaves and fruits was also reduced under SA. These findings provide a novel perspective on Hg accumulation in sweet pepper. They open a door to identify SA signaling pathways to clarify the mechanisms of SA inhibiting Hg accumulation in leaves and fruits. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2023.103283